2017
DOI: 10.1016/j.mayocp.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

REM Sleep Behavior Disorder: Diagnosis, Clinical Implications, and Future Directions

Abstract: Rapid eye movement sleep behavior disorder (RBD) is diagnosed by a clinical history of dream enactment accompanied by polysomnographic rapid eye movement sleep atonia loss (rapid eye movement sleep without atonia). Rapid eye movement sleep behavior disorder is strongly associated with neurodegenerative disease, especially synucleinopathies such as Parkinson disease, dementia with Lewy bodies, and multiple system atrophy. A history of RBD may begin several years to decades before onset of any clear daytime symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
104
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(108 citation statements)
references
References 150 publications
1
104
1
2
Order By: Relevance
“…[22][23][24] Second, a number of hypothalamic-dependent functions, such as sleep and circadian rhythmicity, are severely affected by disease progression. 3,25,26 This hypothalamic involvement could be secondary to dopaminergic 7,27,28 or serotonergic 29 and related to involvement of the autonomic nervous system. 30 In the current study, despite these repeatedly observed features of hypothalamic involvement by others, we were unable to observe gross atrophy of the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Second, a number of hypothalamic-dependent functions, such as sleep and circadian rhythmicity, are severely affected by disease progression. 3,25,26 This hypothalamic involvement could be secondary to dopaminergic 7,27,28 or serotonergic 29 and related to involvement of the autonomic nervous system. 30 In the current study, despite these repeatedly observed features of hypothalamic involvement by others, we were unable to observe gross atrophy of the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic rapid eye movement (REM) sleep behavior disorder (IRBD) is a parasomnia characterized by loss of normal skeletal muscle atonia and dream-enacting behaviors during REM sleep, which affect 0.5% to 2% of the general populations and 5% to 13% of adults older than 60 years (1). RBD is not only frequent in patients with neurodegenerative diseases, but also considered to be a prodromal sign, especially of those with alphasynuclein deposition such as Parkinson's disease (PD) and Lewy body dementia (LBD).…”
Section: Introductionmentioning
confidence: 99%
“…1 The estimated prevalence of RBD is in the range of 0.5% to 2%. 2 Loss of REM sleep atonia is diagnostic for RBD, although probable RBD may be diagnosed on clinical grounds. Obstructive sleep apnea (OSA) is also prevalent in adults and caused by repetitive complete or partial obstruction of the upper airway during sleep.…”
Section: Introductionmentioning
confidence: 99%